Dental Cavity Lining, Composite Resin and Bioceramic: Randomized Clinical Trial - Freitas Pedrosa, Simone Silveira de; Salomé, Geraldo Magela; Maia, Paulo Roberto; Dominguete, Matheus Henrique Lopes; Neto, José Dias da Silva (International Journal of Innovative Research in Medical Science, 2022)
Objective: Evaluation of postoperative sensitivity in posterior teeth restored with CIMMO DTA® liner, in composite resin restorations. Method: Randomized, double-blind clinical trial. There were 20 male participants, with an average age of 20 years. Totaling 70 treated teeth, divided into two groups: Group R (Control n=35), treated with standard restorative procedure. Group D (Study n=35), treated using CIMMO DTA® cement, as an indirect liner, the assessment was performed by a masked examiner. Sensitivity tests were performed before the restorative procedure, at 48 hours, 7, 15 and 30 days after the procedure. The analysis included the pain caused by thermal stimulation: Cold Test (FT); à Horizontal (TPH) and vertical (TPV) percussion; Bite Test (TM) and Pain Decline Time (DD) is measured. Measured through Visual Analog Scale (EVA). Results: All participants returned for postoperative sensitivity tests. Group D had lower pain sensitivity than group R: on the second day, for TPH with p=0.041; TPV with p=0.036; on the fifteenth day, for TPH with p=0.043; TM p=0.021 and on the thirtieth day, for TF with p=0.011. Conclusion: CIMMO DTA® cement, as an indirect liner in dental restorations, decreased postoperative sensitivity.